Identification of an Metabolic Related Risk Signature Predicts Prognosis in Cervical Cancer and Correlates With Immune Infiltration - Shang, Chunliang; Huang, Jiaming; Guo, Hongyan (Frontiers in Cell and Developmental Biology, 2021)
The tumor metabolic reprogramming contribute to the progression and prognosis of cervical cancer (CC). However, the potential remodeling mechanisms of tumor metabolism in the immune microenvironment of CC remain largely unknown. In this study, we first performed microarray analysis to identify differential metabolic gene expression. A novel 5-metabolic-related genes signature comprising P4HA1, P4HA2, ABL2, GLTP, and CYP4F12 was established to better predict prognosis of CC using LASSO-Cox regression analysis. This signature could reveal the metabolic features and monitor the immune status of tumor microenvironment. Among them, P4HA2 was significantly upregulated in CC tissues and negatively correlated with CD8+T cells. Knockdown of P4HA2 inhibitted lipid droplets accumulation and cancer cells invasion. Moreover, P4HA2 knockdown significantly suppressed PD-L1 expression. This study provides a new and feasible method for evaluating the prognosis of CC and explores the potential value to navigate metabolic pathways to enhance anti-tumour immunity and immunotherapy.